(untitled) (Journal of actual problems of jurisprudence, 2025)
Information security is recognized as a comprehensive task, which includes the protection of legally protected information, which forms a single system of national security, as well as a system of appropriate measures of an administrative, organizational, educational and legal nature. The problem of information security as an integral part of national security is constantly being complicated by the processes of penetration of data processing and computing systems in any sphere of society. The interests of the individual in the field of Information contribute to the strengthening of democracy, the creation of a social society, ensuring the interests of the individual in the field of information and the spiritual renewal of Kazakhstan. The interests of the state consist in the sovereignty and territorial integrity of Kazakhstan, political, economic and social stability, as well as the creation of opportunities for the systematic development of the National Information Infrastructure to preserve the integrity of the constitutional system of people and citizens. However, given that the problems of information security are a global problem, the problems of the information Front, information weapons, information threats, information inequalities, information and psychological security, information and energy security, information and economic security have not been studied in the Republic of Kazakhstan. The current legislation of the Republic of Kazakhstan requires systematic legal regulation on the basis of ensuring information security, the formation of the information space, the fight against cybercrime, the protection of information resources and networks. In the article, the authors study the issue of its entry into the International Information and electronic space, protecting the interests of information subjects, taking into account the importance of informatization in the context of the formation and development of qualitatively new socio-economic and political relations in the Republic of Kazakhstan. Key words: information security, security, information and electronic space, national economy, protection of the right to access information, protection of the information system, informatization.